Sexual Knowledge, Desires, and Experience of Adolescents and Young Adults With an Autism Spectrum Disorder: An Exploratory Study - Joyal, Christian C.; Carpentier, Julie; McKinnon, Suzie; Normand, Claude L.; Poulin, Marie-Hélène (Frontiers in Psychiatry, 2021)
Although most persons with an Autism Spectrum Disorder (ASD) wish to have romantic and/or sexual relationships, little is known about self-report sexuality of adolescents/young adults with ASD. In this exploratory study, 172 male and female adolescents/young adults (68 with ASD and 104 without ASD) completed an online version of the Sexual Behaviour Scale-Third edition. Although many more similarities than differences were observed between the groups for views and desires about romantic relationships (e.g., wishing to have a girlfriend/boyfriend), fewer participants with ASD (mostly boys) had experience with a variety of sexual/dyadic behaviors, and approximately half of girls with ASD reported negative sexual experiences. Significantly higher rates of participants with ASD felt their knowledge about sexuality was limited and found it difficult to understand sexual education compared with typically developing (TD) participants. Significantly lower rates of participants with ASD reported that they identify to their assigned gender compared with TD participants. Multiple regressions revealed that being older at first diagnosis and possessing better knowledge about sexuality were significant predictors of both positive and negative sexual experience. This study explores strengths and challenges related with the sexual health of adolescents/young adults with ASD and implications for clinical and educational practice are discussed.